Hybrid Metamaterials Perfect Absorber and Sensitive Sensor in Optical Communication Band - Liu, Xuehan; Li, Keyang; Meng, Zhao; Zhang, Zhun; Wei, Zhongchao (Frontiers in Physics, 2021)
A subwavelength metamaterial perfect absorber (MPA) in optical communication band was proposed and tested using the finite-difference time-domain method. The absorber is periodic and comprises a top layer of diamond silicon surrounded by L-shaped silicon and a gold layer on the substrate. It can achieve dual-band perfect absorption, and one of the peaks is in the optical communication band. By changing the gap (g) between two adjacent pieces of L-shaped silicon, and the thickness (h) of the silicon layer, the resonance wavelength of absorption peak can be tuned. When the incident electromagnetic wave entered the absorber, the metamaterial absorber could almost completely consume the incident electromagnetic waves, thereby achieving more than 99% perfect absorption. The absorption peak reaches 99.986% at 1310 nm and 99.421% at 1550 nm. Moreover, the MPA exposed to different ambient refraction indexes can be applied as plasma sensors, and can achieve multi-channel absorption with high figure of merit (FOM*) value and refractive index (RI) sensitivity. The FOM* values at 1310nm and 1550nm are 6615 and 168, respectively, and both resonance peaks have highly RI sensitivity. The results confirm that the MPA is a dual-band, polarization-independent, wide-angle absorber and insensitive to incident angle. Thence it can be applied in the fields of optical communication, used as a light-wave filter and plasma sensor, and so on.